When Linguistic Elements Contribute to Conceptual Dynamics: The Case of Chinese Students' Pre-instructional Ideas About the Earth. Issue 2 (2nd April 2020) - Tang, Xiaowei; Yang, Liu; Levin, Daniel M.
Abstract: In this study, we explore how cross-linguistic differences can contribute to children's scientific thinking. We compared first and third grade Chinese students' pre-instructional ideas of the earth expressed in clinical interviews with that of their English-speaking and Greek-speaking counterparts (as recorded in the literature). Inspired by a "Complex Dynamic Systems" (CDS) theoretical perspective on cognition and by the literature on "linguistic relativity" we hypothesized that in cases when two language systems offer greatly different linguistic elements, differences can be expected in how these elements interact with other types of conceptual elements. Consequently, such changes in dynamics may lead to variations in system-level conceptual structures emerging from native speakers of different languages. Our findings showed that (1) Chinese students held no flat or dual earth type of pre-instructional ideas about the earth; (2) Chinese students provided significantly more sphere-based responses than their American and Greek counterparts when responding to questions directly addressing the shape of the earth; (3) such cross-linguistic differences largely vanished for questions not directly getting at the shape of the earth, resulting in high frequency of inconsistency when responses to all the interview questions were interpreted as a whole. We discuss the significance and possible implications of these results for research on cross-cultural conceptual development and for teaching and learning science.